Social Normative Bounding and Brand Awareness of E-WOM Intensity in WhatsApp Group Online Community Mekar Arum PKK Group – Bojongsoang - Hassanudin, Abdul Fatah; Murwenie, Ira; Avrianto, Alam; Lestari, Dwirani Fauzi; Puspa, Rahmina (Sainteks: Jurnal Sain dan Teknik, 2024)
Currently, business transactions and communication with customers are carried out through various forms of digital platforms, one of which is using the WhatsApp application on smartphones. This research aims to determine the influence of normative social and brand awareness on the intensity of E-WOM in the WhatsApp Group PKK Mekar Arum - Bojongsoang Group application. This study uses a descriptive statistical approach of Multiple Linear Regression with a research sample of 55 people, each of whom represents one head of family and is a member of the WhatsApp Group under study. The data collection technique was carried out online using the Google Form application and processed with Microsfot Excell 2013 software. This research succeeded in proving that the influence of social norm attachment and brand awareness together had a significant influence on E-WOM intensity of 42.89% while 57.11% are other factors not examined in this study. This means that the PKK Mekar Arum – Bojongsoang Group uses E-WOM on the WhatsApp application mostly to improve communication and interaction between group members. Meanwhile, the intensity of using E-WOM is more aimed at introducing and building brand awareness of the products of PKK Group members and not in an effort to increase sales turnover from products promoted via the WhatsApp group..